The Application of Transfer Knowledge of Exjapan Trainees from Indonesia: Alternative Solution for Rural Development in South Sulawesi And East Java - Devi Riskianingrum; Gusnelly Gusnelly (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2017)
International migration has changed the lives of many people and households in the villages by the value of remittance sent home by migrant workers. Japan is one of many destination countries for Indonesian migrant workers. Since 1993, Indonesian migrant workers have come to Japan on two available schemes, namely the Technical Internship Program (TIP) and the Industrial Training Program (ITP). The remittance in this study does not refer to money but more to knowledge, either in the form of ideas of social cultural values, work ethics, or business ideas obtained by trainees while working in Japan. Trainees not only receive economic but also social remittance whilst working in Japan. These trainees are expected to return with benefits to their social neighborhoods. Hence several subjects are posed in this study which identify the forms and structures of knowledge transferred from Japan to the trainees, the applicability of the knowledge received from the host country to their home country and the challenges and obstacles in managing their economic remittances.